Poligami dalam Perspektif Tafsir Modern Al-Manar - Madiha Dzakiyyah Chairunnisa; Hilman Purnama; Ila Juanda (Fakultas Syari'ah | Institut Agama Islam Darussalam | IAID | Ciamis, Jawa Barat, Indonesia, 2020)
Married is the sunnah of the prophet, although the law of marriage alone for Muslims is determined by its purpose, marriage can be obligatory, sunnah, mubah, even haram is basically adjusted by human intention to get married. The complexity of human life raises several problems in marriage. Among them is the debate about polygamy that has happened so far, which has seized the attention of Muslims, because polygamy is associated with Islamic culture even the sunnah of the prophet. Historically the practice of polygamy has existed since pre-Islamic times. Many figures gave views on polygamy from various aspects related to women.